THE EFFECT OF NUTRITION ON SLEEP QUALITY IN JUNIOR FEMALE (AGED 15-17) WRESTLERS - Tanir, Halil; Cetinkaya, Erkan; Ozdemir, Mehmet; Bozkurt, İbrahim (Acta Scientiae et Intellectus, 2024)
The success of the athlete is based on the achievement of the highest performance in sports. Due to the complex nature of sportive performance, the number of factors that affect performance is quite large. Two of these factors are nutrition and sleep patterns and quality. It is very important for children and young people who are doing sports to have good nutrition and good sleep qualities in order to increase their sporty performance. For this reason, in this research, it was aimed to determine the effect of nutrition on sleep quality in junior female wrestlers who are engaged in wrestling, which is a branch which requires strength, endurance, speed, calmness, concentration and self confidence. The sample of the study consisted of 117 athletes who have participated to the Turkey Junior Female Wrestling Championship (aged 15-17 years) that was organized in Aydin in 2017. The Pittsburgh Sleep Quality Index (PUKI) was used to determine the last 1-month sleep quality of female wrestlers (α=0.77). The Turkish validity and reliability study was reported by Agargun and his friends (1996) as internal consistency coefficient of 0.80. Nutritional habits of female wrestlers were determined using the Nutrition Habits Questionnaire (BAA), consisting of 3 sections and 21 questions. It was found that there was a significant difference between the junior female wrestlers who pay attention to the liquid intake of pre-training and pre-competition and those who did not pay attention to the attentive athletes and this difference is favored by the athletes who pay attention (p<0.05). In addition, there was a significant difference between the athletes in terms of sleep quality (p<0.05), according to the time of the training and the refreshment meal before the competition and the meal after the training-competition. It was seen that the sleep quality of the female wrestlers who were eating 1-2 hours before the training and competitions and who were eating the protein after the training and competitions were better.